Exploring the Use of AI in Text Generation and Writing Assistance Among Junior High School Students in the Philippines - Esparrago-Kalidas, Adeva Jane; Emata, Lea Lilibeth B.; Macaponggis, Sittie Aleah C.; Galon, Warren J.; Velano, Christoff Andrew R.; Moxcir, Ali Abdullah B.; Goyeneche, Angelique D.; Tulner, Ella V.; Cha, Yerim S. (Journal of Languages and Language Teaching, 2025)
This study explores the utilization of Artificial Intelligence (AI) for text content generation and writing task assistance among junior high school (JHS) students in a private school in the Philippines. Employing a quantitative survey research design, data were gathered through an online questionnaire and analyzed using means, t-test, and ANOVA. Results revealed that students exhibited low utilization of AI for text content generation (M = 2.42), primarily due to concerns over academic dishonesty, information accuracy, and risk to grades. Conversely, moderate utilization (M = 2.59) was observed in using AI for writing task assistance, such as grammar checking, idea expansion, and feedback—indicating students’ preference for AI as a tool to enhance, rather than replace, their own work. A significant gender difference (p = 0.0150) was found in text generation, with males using AI more than females, while no significant difference (p = 0.3593) emerged in writing assistance. Grade-level comparisons showed low utilization across all levels for text generation, but significant differences (p = 0.0011) in writing assistance, with higher grade levels showing more frequent use. Findings highlight the need for clear school-wide AI policies and structured guidance to support students in responsibly integrating AI into academic practices. School administrators should establish clear policies, provide A.I. literacy programs, and ensure equitable access to foster ethical and effective use of A.I. in education. Teachers must model responsible engagement with A.I., integrate discussions of its limitations and biases into lessons, and guide students in using it as a learning aid rather than a shortcut. Students are encouraged to verify information, maintain academic integrity, and treat A.I. as a supplement to their own critical thinking and effort. This study fills gaps in existing literature by providing information and analysis about differences in A.I. use among students of varying grade levels, particularly for English writing tasks.